TREATMENT OF PRIMARY MYELOFIBROSIS, WHERE WE STAND TODAY? - Bogdanović, Andrija; Leković, Danijela (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Primary myelofibrosis (PMF) is a clonal hematopoietic neoplastic disease characterized by constitutive complaints, splenomegaly, anemia and very often thrombocytopenia. Aim: To analyze and compare data from clinical trials, focusing on both current and emerging therapeutics.Methods: The analysis of published clinical trials and relevant papers. Results: Currently, the gold standard for treating primary myelofibrosis (PMF) is ruxolitinib, the first-in-class JAK inhibitor (JAKi). It has achieved a ≥35% reduction in spleen volume (SVR) in 41.9% of patients compared to placebo and has led to a >50% improvement in symptoms, as measured by the Total Symptom Score (TSS), in 49.5% of treated individuals. Ruxolitinib is not an ideal drug, as some patients experience worsening anemia, thrombocytopenia, and an increased susceptibility to various infections. Some patients are required to discontinue the treatment or reduce the dosage. Another approved JAK inhibitor, fedratinib, has shown promising results as a second-line treatment following ruxolitinib failure. As a first-line therapy, fedratinib achieved a spleen volume reduction (SVR) of ≥35% in 47% of patients, with a >50% improvement in TSS in 40% of cases. In transfusion-dependent patients, momelotinib has demonstrated good results, showing non-inferiority to ruxolitinib, with similar spleen volume reduction (SVR≥35%) rates of 26.5% compared to 29% with ruxolitinib. Momelotinib treatment reduced transfusion independence by 17% compared to ruxolitinib (66% vs 49%). In thrombocytopenic patients (Plt 50-100 x109/L), pacritinib is the newest therapy; it reduces spleen volume compared to adjusted ruxolitinib dosing without worsening thrombocytopenia. Drugs combined with ruxolitinib (e.g. navitoklaks, pelabresib) have the purpose to improve the outcome, especially in spleen reduction. Conclusion: Treating PMF remains a challenge. While ruxolitinib provides effective disease control in nearly half of patients, new therapies are needed to enhance outcomes both overall and in those with refractory disease.
Keywords: primary myelofibrosis; JAK inhibitors; ruxolitinib; fedratinib; momelotinib; pacritinib